The Effect of Heparin on the Bleeding Time - Hjort, P. F; Borchgrevink, C. F; Iversen, O. H; Stormorken, H (Thrombosis and Haemostasis, 1960)
1. Moderate doses of heparin often prolonged the bleeding time in men, rats and mice. The bleeding was wavelike, and a sensitive method was necessary to demonstrate the prolongation.2. Large doses gave a prolonged bleeding time, and the bleeding was often profuse and continuous.3. Heparin did not produce thrombocytopenia. Moderate doses probably prevent viscous metamorphosis and fibrin formation, resulting in large but inefficient platelet plugs. Large doses may also interfere with the aggregation of platelets, preventing the formation of platelet plugs.